Dose-response relationships for the onset of avoidance of sonar by free-ranging killer whales: - Miller, P.J.O.; Antunes, R.N.; Wensveen, P.J.; Samarra, F.I.P.; Alves, A.C.; Tyack, P.L.; Kvadsheim, P.H.; Kleivane, L.; Lam, F.P.A.; Ainslie, M.A.; Thomas, L. (2014)
Eight experimentally controlled exposures to 1−2 kHz or 6−7 kHz sonar signals were conducted with four killer whale groups. The source level and proximity of the source were increased during each exposure in order to reveal response thresholds. Detailed inspection of movements during each exposure session revealed sustained changes in speed and travel direction judged to be avoidance responses during six of eight sessions. Following methods developed for Phase-I clinical trials in human medicine, response thresholds ranging from 94 to 164 dB re 1 uPa received sound pressure level (SPL) were fitted to Bayesian dose-response functions. Thresholds did not consistently differ by sonar frequency or whether a group had previously been exposed, with a mean SPL response threshold of 142 ± 15 dB (mean ± s.d.). High levels of between- and within-individual variability were identified, indicating that thresholds depended upon other undefined contextual variables. The dose-response functions indicate that some killer whales started to avoid sonar at received SPL below thresholds assumed by the U.S. Navy. The predicted extent of habitat over which avoidance reactions occur depends upon whether whales responded to proximity or received SPL of the sonar or both, but was large enough to raise concerns about biological consequences to the whales. © 2014 Acoustical Society of America